Determination of the role of platelet rich fibrin in the process of regenerating the defect of the vertebral body (experimental study) - Popsuishapka, Kostiantin; Ashukina, Nataliya; Radchenko, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
In the process of developing methods for treating fractures of vertebral bodies, in particular in case of traumatic injury, it is necessary to understand the biology of the processes of formation and reorganization of the regenerate for the possibility of optimizing reparative osteogenesis. Objective: to assess the effect of platelet rich fibrin on the healing of a defect in the vertebral body in experimental rabbits. Methods: simulations were performed in 18 male rabbits aged 4–5 months with an average body weight (4 ± 0.5) kg. A hole defect (diameter and depth of3 mm) in the caudal apophysis of vertebral bodies L3, L4 was created. Defects in 9 rabbits of the experimental group were filled with platelet-rich fibrin, in control (9 animals) defect left unfilled and closed in both cases with a haemostatic «Fibrilar» film. Platelet rich fibrin was prepared by the method of D. M. Dohan Ehrenfest immediately before the operation. After 14 days, 1 and 3 months a histological study was carried out with morphometry of areas of regenerate tissues in the area of traumatic injury. Results: after 14 days in the zone of defect in the vertebral bodies of the rabbits of the control group, granulation and connective tissues predominated. The relative area of the newly formed bone tissue in the defects of the rabbits of the test group was 2.16 times greater (p < 0.01) than in the control group. After 1 month it filled the entire territory of the defect and exceeded the control indicators by 1.2 times (p < 0.05), and in the defects of the vertebral bodies of the rabbits of the control group, the areas of the connective tissue were preserved. After 3 months in rabbits of both groups, the defect zone was filled with lamellar bone tissue. Conclusions: the introduction of platelet rich fibrin into the perforated defect of the vertebral body of the rabbits promotes acceleration of bone formation 14 days and 1 month after injury.